Does Economic Growth in Nepal Cause Electricity Consumption - Dhungel, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
This article examines the causal relationship between the per capita electricity consumption and the per capita real GDP (natural logarithm) during the period 1980-2006 in Nepal using co-integration and vector error correction model. According to the fi ndings, there is a unidirectional causality from per capita real GDP to per capita electricity consumption. Results show that per capita electricity consumption does not cause per capita real GDP. There is an important policy implication of the fi ndings. It is important because it has significant implications from the point of view of energy conservation, Green House Gas emission reduction and economic development. Energy conservation if the government or the power utility industry approves the appropriate national policy for entering into the practical action will enhance economic development in a sustainable basis. Key words: Co-integration; Unit-root; Causality; Energy conservation; Electricity consumption; Economic growth; Nepal DOI: 10.3126/hn.v5i0.2485 Hydro Nepal Vol. 5, July 2009 Page:37-41